(untitled) (Revista de Ensino em Artes, Moda e Design, 2020)
This article reflect about the importance of collaborative design methodologies in the construction of new configurations for the teaching of flat clothing modeling, understanding that, through collaborative means, it is possible to contribute with ac- tivities and solutions from different fields from a new perspective. When designing concepts and formal solutions, the methodology used in this research have followed the assumptions of the qualitative approach, carried out through bibliographic study and Systematic Literature Review. It has been based on conceptual and experimental surveys of research carried out teaching and learning about flat clothing modeling, we present ways of applying collaborative design and its methodological approaches to problems raised in this teaching. The results showed that, from the planning of a collaborative methodology applied to the flat modeling of clothing, it is possible to build projects that, in practice, are more concise and close to the reality of the users, in which this research includes teachers and students from the courses of fashion and clothing design.